2016
DOI: 10.1016/j.renene.2016.04.062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cold conditions on diesel injection processes of biodiesel blends

Abstract: In this article, we report experimental results on the impact of cold conditions on diesel and biodiesel blends injection processes. We focus on cold conditions in view of the new Euro VI standards concerning problems related to cold-start. A Bosch CRI 3.1 piezoelectric injector was used on a typical diesel engine. Five fuel types were tested: diesel, winter diesel, dieselebiodiesel blends (B50), a winter diesel-biodiesel blend (B50(W)) and pure biodiesel (B100). Injection pressures of 30e60 MPa were tested (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Engine operation when its temperature is sub-optimal impacts the exhaust emissions and engine performance parameters [4][5][6]. For example, higher emissions and fuel consumption were reported to be the result of low cylinder wall temperature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Engine operation when its temperature is sub-optimal impacts the exhaust emissions and engine performance parameters [4][5][6]. For example, higher emissions and fuel consumption were reported to be the result of low cylinder wall temperature [7].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the new Euro VI standards for cold start problems, Tinprabath et al [67] conducted an experimental study on the injection process of diesel and biodiesel blend. The authors showed that, under cold conditions, all the fuels used-such as diesel-biodiesel (B50), a winter diesel-biodiesel blend (B50 (W)), and pure biodiesel (B100)-had a discharge coefficient lower than under ambient temperature conditions.…”
Section: Effect Of Fuel Temperaturementioning
confidence: 99%
“…They also reported that reduction in spray cone angle was related to increased spray tip penetration. Tinprabath et al [101] studied the impact of cold flow conditions on biodiesel and its blends with mineral diesel in the fuel injection process. They reported that cold flow conditions induced reduction in discharge coefficient.…”
Section: Spray Evolution Spray Tip Penetration and Fuelmentioning
confidence: 99%